Default, Electoral Uncertainty and the Choice of Exchange Regime - Carsten Hefeker (Hamburg Institute of International Economics (HWWA), 2004)
The paper explores the interaction between debt crises and devaluation. Since the optimal level of devaluation in a crisis depends on the level of debt that has to be serviced, a default makes a devaluation less likely. Expected devaluation depends thus on expectations about default which is also a function of the type of policymaker. Therefore, the decision to devalue can be forced upon the government by adverse expectations about default and the type of policymaker in office. I also explore how these uncertainties affect the policymaker's choice of exchange rate regime.
Keywords: F34; F33; 330; debt crisis; currency crisis; exchange rate regime; Finanzmarktkrise; Auslandsverschuldung; Zahlungsunfähigkeit; Wechselkurssystem; Public Choice; Währungskrise; Theorie